Investigação em estimulação tátil por jatos de CO2 aplicada à comunicação alternativa - Cunha, José Carlos da (2012)
Vibrotactile stimulation has been used to promote alternative communication for people with visual and hearing impairments. The stimuli activate the receptors of the skin that promote the transduction of mechanical stimuli into an electrophysiological response sent to the CNS. Objective: to investigate the response to tactile stimulation by a CO2 jet as a method of alternative. Materials and Methods: a cutaneous stimulation system was developed which yields jets of CO2 on the subject’s skin at stimulating speeds varying from 20 up to 100 mm/s, by means of an injection needle. The instrument acts as a tactile plotter. Tests were conducted in twenty five volunteers without physical and/or cognitive disabilities in whose the psychophysical and cognitive responses were evaluated as well as the rate of correct recognition of nineteen characters applied to the abdominal region, with the stimulus intensity equivalent to three times the threshold of perception. Results: a force perception threshold of 60 mgf was found and the fluxtactile stimulation was performed using a force of 180 mgf. In blind tests, the best rate of correct character recognition had an average of 68 (± 17)%, and occurred at the speed of 40 mm/s and frequency of 1.33 Hz. The characters D, O, M and N have shown the lower average rate of recognition with 29%, 37%, 47% and 51%, respectively, due to the uncertainty generated by their similar morphology, whereas the best rates were observed for letters I, U, J, and B with 87%, 71%, 68% and 65%, respectively. Conclusions: the developed system enabled the experimental research and the acquisition of information necessary for carrying out the research. The results have shown that the psychophysical responses to fluxtactile stimuli are related to the frequency response of the Merkel discs, with maximal performance at 1.33 Hz, corresponding to the speed of the stimulation needle of 40 mm/s. The morphology of the graphical characters and the stimulation needle speed influenced the rates of letters recognition.